A genetic algorithm-based robust approach for type-II U-shaped assembly line balancing problem. (19th January 2023) - Jia, Guangyue; Zhan, Honghui; Peng, Yunfang
U-shaped assembly lines are widely used to implement just-in-time manufacturing. U-shaped assembly line balancing problem is important to improve productivity. Most of the studies ignore uncertainty such as operation times. This study applies robust optimisation method to deal with type-II U-shaped assembly line balancing problem (UALBP-2) under uncertainty. A mathematical programming model is proposed with interval task operation times, and a genetic algorithm is developed to deal with it. A robust solution is defined as the most frequent solution falling within a pre-specified percentage of the optimal solution for different sets of scenarios. The experimental results are compared with the expected solution to verify the feasibility and effectiveness of the robust method.